Peran Public Speaking dalam Kepemimpinan dan Teknologi Informasi dengan Neuro Linguistic Programming - Sawali Wahyu (Publikasi Indonesia, 2023)
The Leadership Training Program organized by the BEM of the Faculty of Computer Science, Esa Unggul University, is carried out with the motto